What a bachelor’s degree is worth today: a comparative survey of income, career advancement, and demographic disparities - Affognon, Don A. (Frontiers in Education, 2026)
This study examines variation in job prospects, earnings, and perceived career alignment across educational attainment and discipline, and evaluates how academic major intersects with race and gender to shape the financial payoffs of a bachelor’s degree. Drawing on survey data from 2,698 U.S. adults (61.7% graduates, 38.3% non-graduates), multiple regression and ANOVA analyses revealed that graduates earn substantially more and are more likely to be employed full-time than non-graduates. Among degree holders, STEM and business majors reported the highest earnings, and humanities and social sciences majors reported lower salaries alongside higher job relevance and stronger career satisfaction scores. Black and Hispanic graduates, and women across majors, earned significantly less than White men holding the same degrees, and the study did not find interaction effects between identity and field of study. These findings confirm that a bachelor’s degree supports upward mobility, and salary gaps by race and gender persist even among participants grouped by major. The results affirm that the economic value of a bachelor’s degree is unevenly distributed across social groups. Policy implications include restructuring federal and institutional aid programs, including the FAFSA system and need-based aid design. The findings are interpreted as descriptive patterns observed within a large cross-sectional survey, without causal or mechanistic claims about labor-market inequality.